Understanding Stunting in Toddlers: Factors Impacting Knowledge Levels among FKIKUAJ Medical Students (2017-2020) - Ongga, Leonardo; Surya, Junita Elvira Pandji; Sasmita, Poppy Kristina (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2023)
Introduction: Stunting is short stature in children due to chronic malnutrition in the first 1000 days of life. Medical students' knowledge plays an important role in preventing stunting. This study aims to determine the factors that are associated with the level of knowledge of FKIK-UAJ students class 2017- 2020 about stunting in children under five. Methods: This is a cross-sectional study of FKIK-UAJ students class of 2017-2020. Data collection using a questionnaire and data analysis using the chi-square test. Results: The total respondents were 136 students with 135 included in the inclusion criteria and 1 person included in the exclusion criteria. The 135 students who filled out the questionnaire were dominated by female gender, class of 2020, clinic education stage, had not participated in the pediatrics clerkship, and had never participated in activities on stunting or child health with the level of knowledge obtained was in the good category 13.3%, sufficient 51.9% and less 34.8%. The chi-square test found that the factors of class (p=0,045), stage of education (p=0,023), and pediatrics clerkship (p=0,039) influenced the level of knowledge about stunting while gender (p=0,688) and activities about stunting or child health (p=0,903) had no effect. Conclusions: The results showed that the factors of class, stage of education, and pediatrics clerkshiphada relationship with the level of knowledge about stunting. Keywords: stunting - knowledge - students.